CHARACTERISTICS AND CORRELATION OF SOURCE ROCKS AND OILS AT JEMAKUR-TABUAN GRABEN, SOUTH SUMATRA BASIN - Syaifudin (PROGRAM STUDI TEKNIK GEOLOGI FAKULTAS TEKNOLOGI MINERAL UPN VETERAN YOGYAKARTA, 2026)
There are differences of argument for determining an oil family at South Sumatra Basin. The first opinion argues that oils were generated from source rocks that were deposited in fluvio-deltaic, shallow marine, and lacustrine environments. In other hand, there is also opinion argues that there are no evidences of source rocks or oils with lacustrine characteristic. The research area is located in the Jemakur-Tabuan Graben, which is considered as syn-rift basin and it is expected to find source rock with fluvio-deltaic, shallow marine, and lacustrine deposit characteristic. The source rocks and crude oils characterizations were conducted by geochemical analysis, including liquid chromatography, gas chromatography, and gas chromatography-mass spectrometry analysis. The source rocks samples were taken from Lemat and Talangakar Formations. Carbon isotope and biomarker analyses were done on the 15 and 14 source rock samples, respectively. Crude oil characterisation was performed in Jemakur-Tabuan Graben, which consist of 15 and 16 samples for carbon isotope and biomarker analyses, respectively. Furthermore, correlation between source rock and crude oil, as well as crude oil to crude oil, was carried out by interpreting the carbon isotope and biomarker data. Geochemical analysis concluded that there is an oil family with lacustrine characteristic in the research area. However, the oil was not generated from source rock of Lemat and Talangakar formations. Source rocks of Lemat and Talangakar Formations show the characteristic of deltaic deposits. There is no correlation between the source rocks (Lemat and Talangakar Formations) and crude oils in Jemakur-Tabuan Graben. The lacustrine source rocks in the research area (as evidenced by the presence of lacustrine oil) was interpreted from source rock of Benakat Formation.